Anne McGee Morganstern, Gothic Tombs of Kinship in France, The Low Countries and England - Maraković, Nikolina (2004)
The author writes a review of a book written by an American author, dealing with a specific tomb type (tomb of kinship) developed in north-western Europe.
Projekt MZOS
ENG